Inflammatory signalling regulates eccentric contraction‐induced protein synthesis in cachectic skeletal muscle. Issue 2 (7th December 2017) - Hardee, Justin P.; Counts, Brittany R.; Gao, Song; VanderVeen, Brandon N.; Fix, Dennis K.; Koh, Ho‐Jin; Carson, James A.
Abstract: Background: Skeletal muscle responds to eccentric contractions (ECC) with an anabolic response that involves the induction of protein synthesis through the mechanistic target of rapamycin complex 1. While we have reported that repeated ECC bouts after cachexia initiation attenuated muscle mass loss and inflammatory signalling, cachectic muscle's capacity to induce protein synthesis in response to ECC has not been determined. Therefore, we examined cachectic muscle's ability to induce mechano‐sensitive pathways and protein synthesis in response to an anabolic stimulus involving ECC and determined the role of muscle signal transducer and activator of transcription 3 (STAT3)/nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NFκB) signalling on ECC‐induced anabolic signalling. Methods: Mechano‐sensitive pathways and anabolic signalling were examined immediately post or 3 h after a single ECC bout in cachectic male Apc Min/+ mice ( n  = 17; 16 ± 1% body weight loss). Muscle STAT3/NFκB regulation of basal and ECC‐induced anabolic signalling was also examined in an additional cohort of Apc Min/+ mice ( n  = 10; 16 ± 1% body weight loss) that received pyrrolidine dithiocarbamate 24 h prior to a single ECC bout. In all experiments, the left tibialis anterior performed ECC while the right tibialis anterior served as intra‐animal control. Data were analysed by Student's t ‐test or two‐way repeated measures analysis of variance with Student‐Newman‐Keuls post‐hoc when appropriate. The accepted level of significance was set at P  < 0.05 for all analysis. Results: Apc Min/+ mice exhibited a cachectic muscle signature demonstrated by perturbed proteostasis (Ribosomal Protein S6 (RPS6), P70S6K, Atrogin‐1, and Muscle RING‐finger protein‐1 (MuRF1)), metabolic (adenosine monophosphate‐activated protein kinase, Peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC‐1α), and Cytochrome c oxidase subunit IV (COXIV)), and inflammatory (STAT3, NFκB, extracellular signal‐regulated kinases 1 and 2, and P38) signalling pathway regulation. Nonetheless, mechano‐sensitive signalling pathways (P38, extracellular signal‐regulated kinases 1 and 2, and Protein kinase B (AKT)) were activated immediately post‐ECC irrespective of cachexia. While cachexia did not attenuate ECC‐induced P70S6K activation, the protein synthesis induction remained suppressed compared with healthy controls. However, muscle STAT3/NFκB inhibition increased basal and ECC‐induced protein synthesis in cachectic Apc Min/+ mice. Conclusions: These studies demonstrate that mechano‐sensitive signalling is maintained in cachectic skeletal muscle, but chronic STAT3/NFκB signalling serves to attenuate basal and ECC‐induced protein synthesis.